Competition between Cation–Solvent and Cation–Anion Interactions in Imidazolium Ionic Liquids with Polar Aprotic Solvents. Issue 7 (14th February 2017) - Marekha, Bogdan A.; Kalugin, Oleg N.; Bria, Marc; Takamuku, Toshiyuki; Gadžurić, Slobodan; Idrissi, Abdenacer
Abstract: The subtle interplay between ion solvation and association was analyzed in mixtures of imidazolium‐based ionic liquids (ILs) with polar aprotic solvents. A site‐specific pattern of cation–solvent and cation–anion interactions was disclosed by a careful analysis of the 1 H and 13 C NMR chemical shift dependence of the mixture composition. It was established that the less polar but more donating γ‐butyrolactone is more prone to establish H‐bonds with the imidazolium‐ring hydrogen atoms of the IL cations than propylene carbonate, particularly at the H 2 site and at high dilutions x IL <0.1. The H 2 site was found to be more sensitive to intermolecular interactions compared to H 4,  5 in the case of ILs with asymmetric anions like trifluoromethanesulfonate (TfO − ) or bis(trifluoromethylsulfonyl)amide (TFSA − ). Abstract : Solvent donicity makes the difference : Accurate NMR chemical shift analysis discloses a subtle balance between ion association and ion solvation in mixtures of imidazolium ionic liquids and polar molecular solvents. The less polar but more donating γ‐butyrolactone favors cation solvation more than propylene carbonate. Anions modulate this effect via competing cation–anion interactions.